(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
This article presents the results of a comparative study of the inactivation of the Newcastle disease virus by formaldehyde, ethylenimine dimer and β-propiolactone. The study found that formaldehyde is the most effective inactivant for the Newcastle disease virus compared to other inactivants. Formaldehyde, at a final concentration of 0.05%, completely loses its infectious activity within 14 hours under certain processing conditions. These conditions include maintaining the temperature around 37 ± 0.5 ℃ and maintaining the pH of the reaction medium in the range of 7.2 to 7.6.